AN ANALYSIS OF FLOUTING MAXIM FOUND IN THE FILM ‘THE HUSTLE’ - Cahyani, Anak Agung Istri Regitha; Utami, Ni Made Verayanti; Putra, I Gusti Bagus Wahyu Nugraha (LPPM Universitas Dhyana Pura, 2020)
ABSTRACTSpeaker intention is an important consideration in conversation to avoid misunderstanding andconstruct a good communication, often referred to as called the cooperative principle. Thisarticle discusses the use of the flouting maxim in the comedy film The Hustle by Chris Addison.Two problems analysed in this study are: (1) The types of flouting maxims found in theutterances among the characters in the film; (2) The motivation by the characters flouted maximin the film. This study uses the qualitative method to describe the phenomena of flouting maximforms found in the film by using the script of the film and also showing the occurrences of eachtype and the motivation by the table to make the analysis more clearly. The findings of thisstudy are presented in an informal and formal way, informally the data presented by thenarrative form in explaining the types and the motivation of flouting maxim and formally usingthe table to show the occurrences of the types and the motivation of flouting maxim. The resultsof this study show the highest occurrences of flouting maxim are flouting maxim of quantity(35%) and flouting maxim of relation (35%) and followed by flouting maxim of manner (20%)and the last is flouting maxim of quality (10%). Collaborative motivation is the highestmotivation used by the characters in the film (55%) and followed by Competitive andConflictive motivation which has the same number of occurrences (20%), the lowest isConvivial motivation (5%).Keywords: Flouting maxim, motivation, filmABSTRAKNiat pembicara adalah hal penting dalam percakapan untuk menghindari kesalahpahamandan membangun komunikasi yang baik atau disebut sebagai prinsip kerja sama. Studi iniberbicara tentang penggunaan pepatah flouting dalam film komedi The Hustle oleh ChrisAddison. Ada dua hal yang dianalisis dalam penelitian ini, yaitu: (1) Jenis maksim mencercayang ditemukan dalam ucapan di antara karakter dalam film; (2) Motivasi oleh para tokohyang melanggar pepatah dalam film. Penelitian ini menggunakan metode kualitatif untukmenggambarkan fenomena bentuk-bentuk pepatah flouting yang ditemukan dalam film denganmenggunakan naskah film dan juga menunjukkan kemunculan masing-masing jenis danmotivasi berdasarkan tabel untuk membuat analisis lebih jelas. Hasil penelitian ini disajikansecara informal dan formal, secara informal data disajikan oleh bentuk naratif dalammenjelaskan jenis dan motivasi pepatah flouting dan secara formal menggunakan tabel untukmenunjukkan kemunculan jenis dan motivasi flouting. Hasil penelitian ini menunjukkankejadian flouting maxim tertinggi adalah flouting maxim of quantity (35%) dan floutingmaxim of relation (35%) dan diikuti oleh flouting maxim of way (20%) dan flouting maxim ofquality ( 10%). Motivasi kolaboratif adalah motivasi tertinggi yang digunakan oleh karakterdalam film (55%) dan diikuti oleh motivasi Kompetitif dan Konflik yang memiliki jumlahkejadian yang sama (20%), yang terendah adalah motivasi Konvivial (5%).Kata kunci: maksim mencerca, motivasi, film